The Significance of Symbolic Devices in Thomas Stearns Eliot's Murder in the Cathedral - Rahmah, Adnan Taher; Jasim, Salman Hayder (International Journal of Language and Literary Studies, 2024)
Thomas Stearns Eliot (1888-1965) was born in St. Louis, Missouri. His family on both sides originally descended from the New England settlers of the seventeenth century. He studied at Harvard University in Massachusetts. He went to Europe in 1910 after he had finished his education. In 1915, he settled in England and earned his living as a schoolmaster and then as a banker in Lloyd's bank in London. He got the British citizenship in 1927. He got a big reputation when he was awarded the Nobel Prize for literature in 1948. He was one of the most important figures in the 20th century literature. He was a poet, a dramatist, and a professional critic. He was classic in literature, catholic in religion and royalist in politics. He was a man that respected traditions, rules and values. Eliot was traditional and conservative. Murder in the Cathedral speaks about the great martyrdom which is always the design of God to the loyal men in order to lead them to the ways of God. It is never the design of Man who has lost his will in the will of God. That is why, Thomas a Becket tries to do his best to wear the crown of martyrdom in order to be a saint in heaven through his personal will but not through God's will. This is the main problem in the play for which T. S. Eliot wants to find a solution by depriving Thomas his human qualities and presenting him as a creature with saintly virtues. The action of the play is only restricted to Thomas' last days.